Structure, morphology, and properties of aliphatic polyurethane elastomers from bio‐based 1,3‐propanediol - Wu, Qing; Ge, Shang; Zhu, Youzhi; Zhu, Yun; Wang, Guiyou (Polymer engineering and science, 2024)
The utilization of biomass resources in the production of bio-based or bio- recycled polyurethanes (Pit) enhances the sustainable development and eco-friendliness of PU. Herein, a series of new bio-based aliphatic polypropylene dicarboxylate) diols were synthesized using bio-based 1,3-propanediol (bio-PDO) and aliphatic dicarboxylic acids with different chain lengths. These bio-based polyester diols and 1,4-butanediol (BDO) reacted with 4,4'-dicyclohexylmethane diisocyanate to produce aliphatic PU elastomers (PUEs). The study aimed to evaluate the impact of the structure of polypropylene dicarboxylate) diols on the architecture, morphology, mechanical properties, and degradation of PUEs, thereby expanding the application of bio-PDO. The results indicate a strong correlation between the degree of microphase separation, tensile properties, and degradation behavior of the synthesized PUEs and the number of methylene groups in the repeating unit of the polypropylene dicarboxylate) diols. Notably, the PUE derived from polypropylene pimelate) did demonstrates the highest level of microphase separation and superior elasticity properties because of the high flexibility of the polyester. On the other hand, PUE prepared from polypropylene succinate) did exhibits the fastest degradation performance due to its high density of ester groups. Bio-PDO based polyester diols show significant potential as raw materials for PUEs with biodegradable and adjustable mechanical properties.